Dear friends, Please read our latest blog post for an important announcement about the website. ❤, The Socratic Team

How do you evaluate #9- 4( x + 1) - 3= 9+ 2( 4- 2x ) - 16#?

1 Answer
Write your answer here...
Start with a one sentence answer
Then teach the underlying concepts
Don't copy without citing sources
preview
?

Answer

Write a one sentence answer...

Answer:

Explanation

Explain in detail...

Explanation:

I want someone to double check my answer

Describe your changes (optional) 200

1
May 2, 2018

Answer:

No Solution or #cancel(0)#.

Explanation:

#9-4(x+1)-3 = 9+2(4-2x)-16#

First, combine like terms:
#6 - 4(x+1) = -7+2(4-2x)#

Now distribute/expand:
#6 - 4x - 4 = -7 + 8 - 4x#

#2 - 4x = 1 - 4x#

Subtract #color(blue)2# from both sides of the equation:
#2 - 4x quadcolor(blue)(-quad2) = 1 - 4x quadcolor(blue)(-quad2)#

#-4x = -1 - 4x#

Add #color(blue)(4x)# to both sides of the equation:
#-4x quadcolor(blue)(+quad4x) = -1 - 4x quadcolor(blue)(+quad4x)#

#0 = -1#

We don't have variables anymore! Now what we do is see if this equation is true. #0# does NOT equal to #-1#, so it is false.

When it is false, that means there is No Solution or #cancel(0)#.

Hope this helps!

Was this helpful? Let the contributor know!
1500